Treatment options for patients with hormone receptor-positive, HER2-negative advanced-stage breast cancer: maintaining cyclin-dependent kinase 4/6 inhibitors beyond progression - Horani, Malek; Abdel-Razeq, Hikmat (Frontiers in Oncology, 2023)
Breast cancer is the most commonly diagnosed cancer in women worldwide. Over the past decade, the treatment paradigm for patients with metastatic breast cancer (MBC) have taken an important shift towards better survival and improved quality of life (QOL), especially for those with hormone receptor (HR) positive disease which represent the majority of breast cancer subtypes. The introduction of cyclin-dependent Kinase 4/6 (CDK4/6) inhibitors in the upfront therapy of such patients have resulted in dramatic improvement in progression-free survival (PFS) and overall survival (OS), too. However, almost all patients would, sooner or later, develop disease progression and necessitate transition to different line of treatment that may include chemotherapy. The idea of maintaining CDK4/6 inhibitors beyond disease progression seems attractive, as this approach has the potential to improve outcome in this setting despite the fact that the true benefit, in terms of survival, might not carry the same weight as it initially does. Researchers have been investigating potential mechanisms of resistance and identify possible biological markers for response after disease progression. Much of the available data is retrospective, however, few randomized clinical trials were recently published and few more are ongoing, addressing this point. In this paper, we intend to review the available published studies investigating the potential role for keeping CDK4/6 inhibitors in play beyond disease progression.